Internet of Things (IoT)-Based Water Quality Monitoring System Design for Tilapia Fish Farming Ponds - Putu Erawati; Dianradika Prasti; Tri Bondan Kriswinarso (Brilliance: Research of Artificial Intelligence, 2025)
This study aimed to develop an Internet of Things (IoT)-based water quality monitoring system for tilapia cultivation ponds at Varel Collection. Farmers previously monitored pond water manually, which was often neglected due to their agricultural activities, leading to poor water conditions and negative impacts on fish growth. To overcome this issue, a prototype system was designed to enable real-time monitoring of water parameters using IoT technology integrated with the Blynk platform. The research applied a Research and Development (R&D) approach with a Prototype method. The system was built using NodeMCU ESP32 as the main microcontroller, integrated with several sensors including a pH sensor, DS18B20 temperature sensor, and a turbidity sensor to measure water quality parameters. Data from these sensors are processed and transmitted to the Blynk application, allowing farmers to remotely monitor pond conditions via the internet. Supporting tools included Fritzing for design, Arduino IDE for programming, and hardware components such as adapters, jumper cables, and enclosures. Evaluation by three experts indicated that the system achieved an average feasibility index of 95.93%, categorized as “very good.” These findings show that the IoT-based monitoring system is functional, feasible for aquaculture use, and has strong potential for further development in real-time water quality management.